2006
DOI: 10.1007/s10286-006-0331-x
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine and behavioural responses to CO2 inhalation in central versus peripheral autonomic failure

Abstract: Multiple system atrophy (MSA) and pure autonomic failure (PAF) represent distinct pathological models of autonomic failure in humans. We have investigated the neuroendocrine, behavioural and autonomic cardiovascular responses to the 35% CO2 challenge. Nine patients with MSA, nine with PAF and five control subjects received a single breath of 35% CO2. Peripheral autonomic failure (i.e., PAF) was associated with significantly lower resting noradrenaline levels. All groups demonstrated a significant pressor respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 36 publications
2
10
0
Order By: Relevance
“…In all our cases, dementia developed more than four years after onset of Parkinsonism. Thus, our population is different from that of patients with dementia with Lewy bodies (DLB), in whom dementia typically occurs within one year of onset of Parkinsonism [19]. The mean time interval between the onset of motor symptoms and the onset of dementia was 9.6 ± 3.4 years (range 6-16 years).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In all our cases, dementia developed more than four years after onset of Parkinsonism. Thus, our population is different from that of patients with dementia with Lewy bodies (DLB), in whom dementia typically occurs within one year of onset of Parkinsonism [19]. The mean time interval between the onset of motor symptoms and the onset of dementia was 9.6 ± 3.4 years (range 6-16 years).…”
Section: Resultsmentioning
confidence: 99%
“…A relationship between autonomic failure, including OH, and neuropsychological dysfunction has been recently reported [16,19] This is an important issue, as there is evidence suggesting a bi-directional interactions between cognitive and autonomic process [15] and neurovascular instability, including OH, has been reported in neurodegenerative dementias [4]. It has been proposed that brain hypoperfusion in the setting of hypotension may result in subcortical ischemic vascular dementia [24].…”
mentioning
confidence: 97%
“…However, the analysis of self-reported anxiety varies between peak anxiety (Wetherell et al, 2006), rate of anxiety increase during the task (Kaye et al, 2004), and the presence of a panic-like event (Kaye, Young, Mathias, Watson, & Lightman, 2006), which have all supported the associated of CO 2 hypersensitivity with anxiety disorders (Vickers et al, 2012). Moreover, the manifestation of anxiety and fear processes may be obscured by existing assessments of CO 2 hypersensitivity.…”
mentioning
confidence: 99%
“…In another study, no association was found between the disease severity and orthostatic hypotension 21 . While there are studies which have not found an association between autonomic dysfunction and cognitive exposure 19,22 , there are also studies which show an association between the two 23 . Prospective studies are needed to show the association between autonomic dysfunction and cognitive exposure.…”
Section: Resultsmentioning
confidence: 99%